PROSEDUR MEDIASI DI PENGADILAN NEGERI DALAM MENYELESAIKAN SENGKETA PERDATA - Hj. Jauhariah (Justici, 2019)
The Mediation Procedure in the District Court is as follows: a) After the case is numbered, and the Panel of Judges has been appointed by the Chairperson, then the Panel of Judges determines the mediator for mediation; b) After the parties are present, the Assembly submits the determination of mediation to the mediator and the parties in question; c) Subsequently the mediator advises the litigant parties so that the case ends with a peaceful way by trying to reduce the losses of each litigant party; d) The mediator is on duty for 21 calendar days, successful peace or not on the 22nd day must return to the Assembly which gives the determination.